Testing for unit roots in three-dimensional heterogeneous panels in the presence of cross-sectional dependence (2008)
The cross-sectionally augmented IPS (CIPS) test of Pesaran (2007) is extended for a three-dimensional (3D) panel. This 3D-CIPS test is correctly sized. However, a bootstrapped IPS test has better power performance than the 3D-CIPS, except for high levels of cross-sectional dependency. © 2008 Elsevier B.V. All rights reserved.